The level of knowledge of the healthier lifestyle and eating habits in a group treated in the surgical ward - Woźniak, Iwona (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2013)
Aim of the study : The aim of this study was to assess the nutritional habits of hospitalized patients. Material and methods: 100 patients hospitalized in the Department of General, Vascular and Transplant Surgery, Medical University of Silesia were enrolled to the study. The study was performed using a questionnaire. Participation in the study was voluntary and anonymous, and everybody could withdraw from the study at any time. Patients came from different regions of the country. Results : The analysis of the material shows that the most frequent diagnosis requiring surgery was: dissecting aneurysm of the aorta (29 persons) and acute ischemia of the limb (20 persons). The majority of respondents (85%) had cardiovascular diseases diagnosed, 67% were overweight, and the 49% did not know the healthy eating pyramid. Conclusions : The level of knowledge of respondents about the healthier lifestyle and healthy eating pyramid is similar irrespective of the age, education and occupational activity.